Factors affecting the forecasted profitability of construction enterprises listed on the Vietnamese stock market - Nguyet, Nguyen Minh; Kien, Tran Trung; Thu, Ho Thi Hoai; Ha, Pham Thi Thu (Edelweiss Applied Science and Technology, 2025)
The study was conducted to analyze the factors affecting the forecasted profitability of construction enterprises listed on the Vietnamese stock market in the upcoming year. Using E-view software for quantitative analysis, a panel data regression model was developed. The White, Hausman, and Wald tests were employed to select the appropriate model based on tests of the pooled ordinary least squares model (POLS), finite element model (FEM), and random effects model (REM). The study established a regression model to determine the relationship of internal factors influencing the future profitability of 126 listed construction enterprises. The results indicated that the asset growth rate was positively correlated with profitability in the following year, whereas three factors—profitability in the previous year, company size in the previous year, and dividends paid in the previous year—were negatively correlated with future profitability. Additionally, the study found that the capital structure, net working capital, and revenue structure of listed construction enterprises in Vietnam from 2019 to 2024 did not significantly affect forecasted profitability. Based on these findings, several recommendations are proposed to assist business managers in predicting future profitability more accurately.